1998
DOI: 10.1103/physrevd.57.265
|View full text |Cite
|
Sign up to set email alerts
|

On-shell-improved lattice QCD with staggered fermions

Abstract: By using Symanzik's improvement program, we study on-shell improved lattice QCD with staggered fermions. We find that there are as many as 15 independent lattice operators of dimension of six (including both gauge and fermion operators) which must be added to the unimproved action to form an O(a 2 ) improved action. Among them, the total number of dimension-6 gauge operators and fermion bilinears is 5. The other 10 terms are four-fermion operators. At the tree-level and tadpole-improved tree-level, all the 10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…It was also observed that this interaction is a short-distance lattice artifact of relative order a 2 which can be removed by tree-level modifications of the lattice action. A more recent study, however, contradicts this conclusion by arguing that the one-gluon mechanism is redundant in O(a 2 ), and therefore that flavor-changing interactions are higher order in a or α s [3]. In this paper we resolve this contradiction by showing that one-gluon exchange is indeed responsible for the dominant flavor-changing interaction, as originally argued; the flavor-changing effects are not redundant in O(a 2 ).…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…It was also observed that this interaction is a short-distance lattice artifact of relative order a 2 which can be removed by tree-level modifications of the lattice action. A more recent study, however, contradicts this conclusion by arguing that the one-gluon mechanism is redundant in O(a 2 ), and therefore that flavor-changing interactions are higher order in a or α s [3]. In this paper we resolve this contradiction by showing that one-gluon exchange is indeed responsible for the dominant flavor-changing interaction, as originally argued; the flavor-changing effects are not redundant in O(a 2 ).…”
Section: Introductionmentioning
confidence: 51%
“…Thus the effects of these exchanges can be canceled by adding four-quark interactions to the quark action [1]. The contact terms required at tree-level were explicitly constructed in [3]; these could be added to the staggered-quark action and the leading flavor-changing interactions removed. There is, however, a simpler modification of the action that accomplishes the same goal.…”
Section: Flavor-changing Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice it is easiest to first determine all allowed lattice operators of dimension ≤ 6, as in Refs. [15,6], and then map these onto continuum quark-level operators [6]. Next one maps the continuum quark-level operators onto chiral operators describing the PGB sector.…”
Section: Nlo Staggered Chiral Lagrangianmentioning
confidence: 99%